2019
DOI: 10.5152/tud.2019.03710
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI fusion-guided prostate biopsy in biopsy naive patients: Preliminary results from 80 patients

Abstract: A P e e r -R e v i e w e d B i m o n t h l y J o u r n a l I S S N 2 1 4 9 -3 2 3 5 • E I S S N 2 1 4 9 -3 0 5 7 I n d e x e d i n P u b M e d , W e b o f S c i e n c e a n d S c o p u s İsa Burak Güney, et al., The role and effect of FDG-PET/CT on patient management and restaging of bladder carcinoma. Page: 423 A P e e r -R e v i e w e d B ı m o n t h l y J o u r n a l A P e e r -R e v i e w e d B ı m o n t h l y J o u r n a l A P e e r -R e v i e w e d B ı m o n t h l y J o u r n a l A P e e r -R e v i e w e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…In a prospective study by Murphy et al involving biopsy-naïve 39 patients who underwent fusion biopsy, PI-RADS scores of detected lesions were found to be significantly higher than benign lesions (25). Sonmez et al reported higher rates of PCa detection in patients with PI-RADS-4 or 5 lesions than those with PI-RADS-3 lesions (26). In our study, in accordance with the literature, it was observed that detected cancer rates in PIRADS-4 and 5 lesions were higher than PI-RADS-3 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study by Murphy et al involving biopsy-naïve 39 patients who underwent fusion biopsy, PI-RADS scores of detected lesions were found to be significantly higher than benign lesions (25). Sonmez et al reported higher rates of PCa detection in patients with PI-RADS-4 or 5 lesions than those with PI-RADS-3 lesions (26). In our study, in accordance with the literature, it was observed that detected cancer rates in PIRADS-4 and 5 lesions were higher than PI-RADS-3 lesions.…”
Section: Discussionmentioning
confidence: 99%
“…MpMRI-guided FPB has been shown to provide successful outcomes in patients with a history of negative biopsy and has become a well-established biopsy technique [5-6]. Additionally, it has recently emerged as a successful technique in biopsy-naïve patients as well [7-9]. As expected, based on these data, the findings of the present study that evaluated both biopsy-naïve and previous negative biopsy patients indicated that TB had the lowest number of core and CB had the highest (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…FPB is recommended primarily for repeat biopsy in patients with a clinical suspicion of PCa whose initial prostate biopsies were negative and for follow-up biopsy in PCa patients on active follow-up and for patients who have a clinical suspicion of recurrence after local minimally invasive treatment (e.g., radiotherapy or high-intensity focused ultrasound (HIFU)) [5-6]. Additionally, FPB has been recently shown to provide effective outcomes in biopsy-naïve patients [7-9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one of our previous studies, we prospectively evaluated our early results of 80 patients and we found that the FPB administered in CB could be a successful technique in biopsy-naïve patients [ 10 ]. In the present study, we aimed to evaluate clinical outcomes of another cohort of 400 biopsy-naïve patients with a PSA level of 2-10 ng/ml.…”
Section: Introductionmentioning
confidence: 99%